Comparing the environmental impact of poultry manure and chemical fertilizers - Kiss, Nikolett Éva; Tamás, János; Mannheim, Viktoria; Nagy, Attila (Frontiers in Built Environment, 2023)
One of the challenges in livestock production is the significant volume of manure generated, which must be appropriately managed to mitigate its environmental impacts. Untreated manure poses a potential hazard to soil, surface water, groundwater, and human and animal health. Based on the life cycle assessment (LCA) method, the research aims to evaluate the ecological load of compostedpelletized poultry litter (CPPL) in maize and winter wheat production. Furthermore, the environmental loads of CPPL applications are compared with those of other N, P, and K fertilizers. The research study utilized the openLCA software with the Agribalyse 3.1 database to calculate eleven impact categories. In the case of maize, only ozone depletion has higher emissions. For winter wheat production, scenarios where the P fertilizer was MAP had lower impacts for NPK combinations. While for the CPPL, fuel was the main contributor to loads, for the NPK fertilizer scenarios, energy use for fertilizer production contributed more. The results can be relevant to the burdens of using different nutrient replacement products and creating diverse feed mixtures. The application of CPPL promises to reduce the burden of crop production and, consequently, feed production. Additionally, it allows for the recovery of manure not usable by the livestock industry.